2012
DOI: 10.1177/0269881112443743
|View full text |Cite
|
Sign up to set email alerts
|

Δ9tetrahydrocannabinol impairs visuo-spatial associative learning and spatial working memory in rhesus macaques

Abstract: Cannabis remains the most commonly abused illicit drug and is rapidly expanding in quasi-licit use in some jurisdictions under medical marijuana laws. Effects of the psychoactive constituent Δ9tetrahydrocannabinol (Δ9THC) on cognitive function remain of pressing concern. Prior studies in monkeys have not shown consistent evidence of memory specific effects of Δ9THC on recognition tasks and it remains unclear to what extent Δ9THC causes sedative versus specific cognitive effects. In this study, adult male rhesu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 66 publications
4
24
0
Order By: Relevance
“…Model comparison showed that Δ 9 -THC produced a dose-dependent increase in the slope of the forgetting function. This effect is consistent with an increase in the rate of forgetting reported in DMTS with humans (Lane et al, 2005), DMTS/DNMTS with rodents (Hampson and Deadwyler, 1999) and other working memory procedures with rhesus monkeys (Taffe 2012). Acute administration of methylphenidate failed to systematically alter the forgetting functions over a range of behaviorally active doses.…”
Section: Discussionsupporting
confidence: 87%
“…Model comparison showed that Δ 9 -THC produced a dose-dependent increase in the slope of the forgetting function. This effect is consistent with an increase in the rate of forgetting reported in DMTS with humans (Lane et al, 2005), DMTS/DNMTS with rodents (Hampson and Deadwyler, 1999) and other working memory procedures with rhesus monkeys (Taffe 2012). Acute administration of methylphenidate failed to systematically alter the forgetting functions over a range of behaviorally active doses.…”
Section: Discussionsupporting
confidence: 87%
“…THC impairs performance in a variety of learning- and memory-based operant conditioning tasks in rhesus monkeys (Schulze et al, 1988; Winsauer et al, 1999; Taffe, 2012b). The effects of THC on cognitive performance generally overlap with the doses of THC that produce hypothermia and disruptions in fixed ratio responding in rhesus monkeys (McMahon et al, 2005), although direct comparisons across studies are complicated by differences in THC treatment history, route of administration, and pretreatment time.…”
Section: Discussionmentioning
confidence: 99%
“…The procedure used was derived from the self-ordered spatial search (SOSS) task described in Weed et al . (1999) which is sensitive to amnestic drugs such as ketamine and scopolamine (Taffe et al, 1999, Taffe et al, 2002), as well as Δ 9 -tetrahydrocannabinol (Taffe, 2012). Within each session, trials were presented in the following order: 15 2-stimulus trials → 15 3-stimulus trials → 15 2-stimulus trials → 15 3-stimulus trials.…”
Section: Methodsmentioning
confidence: 99%